Politeness in Language from the Perspective of Unggah-Ungguh Culture on the X Account @Jawafess - Fauzi, Nur; Dui Putra, Libra (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Politeness in language, particularly in the context of the unggah-ungguh culture, plays an important role in social interaction within Javanese society. The use of language that reflects norms of politeness indicates respect and appreciation for others, which is at the core of Javanese culture. In the era of globalization and the development of social media, communication phenomena have undergone significant changes, with many individuals tending to neglect language ethics in online interactions. This research aims to identify and describe forms of politeness in language used on the X account @Jawafess. By utilizing the perspective of unggah-ungguh culture, it is hoped to reveal how the Javanese community continues to uphold values of politeness even while operating in the unrestricted realm of social media. This study employs a qualitative research method, with data and research findings presented in verbal form. Data will be presented using the interactive data analysis model developed by (Miles & Huberman, 1994). The data analysis consists of data reduction, data presentation, and conclusion drawing. In this study, a total of 63 comment data have been identified for analysis to examine language politeness within the context of unggah-ungguh culture. The aim of this analysis is to evaluate how the values of politeness inherent in Javanese culture are implemented in online communication. The findings of this analysis are expected to provide insights into how the Javanese community, particularly the younger generation, adapts to language culture in the era of social media. Additionally, this research can serve as a reference for the development of language and culture education programs that emphasize the importance of politeness in various contexts, especially on online platforms. Thus, the analysis of these 63 comment data not only highlights language practices on social media but also reflects the dynamics of culture and social values that need to be maintained and developed in modern communication.